Polemik Ahmadiyah Di Media Online: Studi pada Weblog Interaktif Kompasiana - Gun Gun Heryanto (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2016)
Internet as a new media is a communication channel that can be a new public sphere. Especially after the migration of web 1.0 to web 2.0, internet users are connected to many social networking sites and interactive weblog to share informations, ideas and thought. It also allows the debate surrounding the Ahmadiyya get space between netizens. Polemic about Ahmadiyya no longer solely a matter of aqidah as a matter of prophecy, al Mahdi and al Masih, revelation, caliphate and jihad but also a matter of Human Rights (HAM) and the law. We need to map out the themes of the talk surrounding the Ahmadiyya among internet users as well as the need to know the context and dynamics of the evolving discourse on new media. This study traced 100 posts written by Internet users in Kompasiana during 2008-2012 as well as the data from the focus group discussion (FGD) with Kompasianer.